2009
DOI: 10.1007/s00268-008-9893-1
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Somatostatin Receptor 5‐Regulated Gene Expression Profiles in Murine Pancreas

Abstract: A specific set of genes linked to a wide range of cellular functions such as islet proliferation, apoptosis, angiogenesis, and tumorigenesis were either upregulated or downregulated in SSTR5-deficient male mice compared with their expression in wild-type mice. Therefore, these genes are potential SSTR5-regulated genes during normal pancreatic development and functional maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…SSTR5 is also involved in the regulation of angiogenesis (Zatelli et al, 2001) and apoptosis (Qiu et al, 2006; Wang et al, 2013). This is consistent with microarray studies of pancreatic RNA from SSTR5 −/− mice in which ablation of SSTR5 results in up-regulation of proliferated and angiogenic genes and suppression of apoptotic genes (Patel et al, 2009). …”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…SSTR5 is also involved in the regulation of angiogenesis (Zatelli et al, 2001) and apoptosis (Qiu et al, 2006; Wang et al, 2013). This is consistent with microarray studies of pancreatic RNA from SSTR5 −/− mice in which ablation of SSTR5 results in up-regulation of proliferated and angiogenic genes and suppression of apoptotic genes (Patel et al, 2009). …”
Section: Introductionsupporting
confidence: 88%
“…SSTR5 has been shown to regulate a specific set of genes linked to cell proliferation, apoptosis, angiogenesis, immunity and tumorigenesis (Patel et al, 2009). PDX-1 also regulates a group of genes related to cell proliferation, apoptosis, invasion and angiogenesis (Liu et al, 2011).…”
Section: Perspectivementioning
confidence: 99%
“…12 A recent study may shed additional light on racial differences, discovering that somatostatin subtype receptor (SSTR5) is recognized as a regulator of pancreatic tissue and that genotype differences in SSTR5 may exist by race. 13–15 Studies have not adequately assessed the contribution of behavioral or genetic risk factors to racial differences in incidence.…”
Section: Resultsmentioning
confidence: 99%
“…It is not known whether somatostatin is also able to regulate its own expression, but there are some indications that this might be possible. The binding of somatostatin to SSTR5 mediates an inhibitory effect on islet cell survival and insulin expression [126,127]. Zhou et al [128] reported that SSTR5-induced signaling is linked to PDX1.…”
Section: Putative Autocrine Feedbackmentioning
confidence: 99%